Implication Of Construction Activities Towards Environment - Ashvin Naidu, Retna Kumar (2020)
Construction in the world is moving rapidly to improve the quality of life. The rapid movement of construction to better the living standards has taken a toll on the environment. Environmental and political mobilization to address the impacts construction has risen in recent years. There are various industries that are redefining their goals and perspectives and making their operations socially more acceptable and resource-wise sustainable. At the same time, they are trying to retain and reinforce their identity as vehicle of economic growth and national development. The objectives of this research is to highlight the implications of construction activities towards the environment and to find possible resolution to reduce the impact of construction towards Mother Nature. A questionnaire survey was carried out and 109 out of 150 sets of questionnaire were collected from the targeted respondent to understand the implications towards the environment faced during construction phase as well as possible mitigation methods to reduce impacts from construction activity towards environment. A comprehensive analysis was carried out to further understand the data collected. It was found out that noise was a primary contributor as an impact towards the environment from construction. Construction sites also polluted water due to soil erosion from construction sites and was found as one of the major factors towards endangering the environment. From this research also, it was found that by imposing sustainable policies and guidelines to ensure sustainable construction was the best way to help mitigate the impacts of construction towards the environment. By recognising the major factors that causes impact to the environment and possible mitigation methods to reduce impact towards the environment from a more sustainable construction perspective is what this research can contribute to the construction industry.